2022
DOI: 10.1021/acs.jpcb.2c01851
|View full text |Cite
|
Sign up to set email alerts
|

Shape Resonances in DNA: Nucleobase Release, Reduction, and Dideoxynucleoside Products Induced by 1.3 to 2.3 eV Electrons

Abstract: Understanding the details of DNA damage caused by high-energy particles or photons is complicated by the multitude of reactive species, arising from the ionization and dissociation of H2O, DNA, and protein. In this work, oligonucleotides (ODNs) are irradiated with a beam of low-energy electrons of 1.3 to 2.3 eV, which can only induce damage via the decay of shape resonances into various dissociative electron attachment channels. Using LC–MS/MS analysis, the major products are the release of nonmodified nucleob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…In the past two decades, a large number of experimental studies have been reported in the literature which have investigated the interaction of LEEs with DNA. One of the first experimental studies on electron attachment-induced DNA strand breaks was reported by Sanche and co-workers, where dry DNA, having only the structural water molecules intact, was exposed to electrons having kinetic energies as low as 3.5 eV. Gel electrophoresis of the DNA sample was performed to quantify the damaged (SSBs and DSBs) and undamaged DNA.…”
Section: Mechanism Of Tni-induced Dna Damagementioning
confidence: 99%
See 3 more Smart Citations
“…In the past two decades, a large number of experimental studies have been reported in the literature which have investigated the interaction of LEEs with DNA. One of the first experimental studies on electron attachment-induced DNA strand breaks was reported by Sanche and co-workers, where dry DNA, having only the structural water molecules intact, was exposed to electrons having kinetic energies as low as 3.5 eV. Gel electrophoresis of the DNA sample was performed to quantify the damaged (SSBs and DSBs) and undamaged DNA.…”
Section: Mechanism Of Tni-induced Dna Damagementioning
confidence: 99%
“…LC-MS/MS analysis of the products further showed that only a minor quantity of the products was formed due to base release. However, when the model DNA systems were changed to a 16-mer oligonucleotide, unaltered nucleobase formed due to sugar–nucleobase rupture was the major DEA product . They attribute this observation to the delocalization of the additional electron within the long DNA strand.…”
Section: Summary Of Dna Strand-break Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many experimental and theoretical works have been conducted to unravel the intricacies of the process of LEE attachment to DNA and its subsequent damage. Since DNA is a macromolecule, the entire DNA or RNA strand cannot be simulated using the existing quantum chemical techniques due to computational bottlenecks.…”
Section: Introductionmentioning
confidence: 99%